Lipid Nanoparticles for Broad‐Spectrum Nucleic Acid Delivery. (26th August 2021) - Hejdankova, Zuzana; Vanek, Vaclav; Sedlak, Frantisek; Prochazka, Jan; Diederichs, Audrey; Kereïche, Sami; Novotna, Barbora; Budesinsky, Milos; Birkus, Gabriel; Grantz Saskova, Klara; Cigler, Petr
Abstract: Lipid nanoparticles (LNPs) are the most advanced nonviral modality for nucleic acid (NA) delivery, and have recently gained enormous attention in the fields of RNA therapeutics and vaccine development. Here, ionizable adamantane‐based lipidoids named XMaNs, which circumvent the usual need for laborious optimization of LNP components for highly diverse types of NAs, are described. The non‐toxic XMaN6 lipidoid is highly versatile in entrapment and delivery of siRNA, mRNA, plasmid DNA, and a cyclic dinucleotide. XMaN6‐based LNPs efficiently deliver: 1) siRNA into human primary hepatocytes and cell lines that are hard‐to‐transfect; 2) mRNA into mouse liver; 3) plasmid DNA; 4) 2′, 3′‐cGAMP into cells and activated the cGAS‐STING pathway three orders of magnitude more efficiently than 2′, 3′‐cGAMP alone. To our knowledge, such universality in delivering different NA types has not been previously described and can accelerate translation of LNPs into the clinic. Abstract : Adamantane‐based lipid nanoparticles named XMaNs transfect safely in vitro and in vivo a wide range of nucleic acid types. mRNA, siRNA, pDNA, and cyclic dinucleotides are efficiently delivered to cells that are difficult to transfect, including human primary hepatocytes. XMaNs circumvent the usual need for laborious optimization of lipid nanoparticles for successful delivery of nucleic acids of various origins.